Removal of iron from acidic aluminum chloride solutions by solvent extraction using D2EHPA - Turan, Mucevher; Aydemir, Muhammed Kursat; Turan, Mehmet Deniz; Erdemoglu, Murat (Gazi Univ, 2026)
This study presents a method for purifying acidic aluminum chloride solutions, specifically targeting the removal of iron (Fe) impurities to enhance the quality of alumina produced from aluminum silicate clay. The research employed solvent extraction using di(2-ethylhexyl)phosphoric acid (D2EHPA) dissolved in kerosene as the extracting agent. The investigation was conducted using both simulated solutions and actual leach solutions derived from hydrochloric acid processing of clay ore. Key experimental parameters included reaction time, organic-to-aqueous phase ratio (O/A), and the concentrations of HCl, D2EHPA, iron, aluminum, potassium, and sodium. The results demonstrated that the efficiency of iron extraction improved significantly with increased concentrations of both HCl and the D2EHPA extractant. AHowever, the presence of excessive chloride ions was found to have a negative impact on this efficiency. Analysis using a McCabe-Thiele diagram indicated that a high iron removal rate exceeding 91% necessitates a two-stage extraction process. The study identified optimal conditions for this purification: a mixing time of 30 minutes, a D2EHPA concentration of 20%, and an equal organic-to-aqueous phase ratio (O/A = 1:1). Under these precise conditions, the process achieved a remarkable iron removal efficiency of 95.58%, demonstrating its high effectiveness for this specific application.
Keywords: Acidic aluminum chloride solutions; Iron removal; Solvent extraction; D2EHPA